Uniform feelings: scenes from the psychic life of policing - Jackson, Jessi Lee (University of Michigan Press, 2022)
Introduction: Compass -- 1. Gun: Relationships and Revolvers -- 2. Statistic: Frameworks of Precarity in Policing -- 3. Guidebooks: Police Psychology at the Scenes of State Violence -- 4. Manual: The Nonperformativity of Implicit-Bias Training -- 5. Museum: Heroic Fantasies at the American Police Hall of Fame -- 6. Memorial: Blue Mourning at the National Law Enforcement Officer's Memorial -- Conclusion: Abolitionist Psychologies -- Notes -- Bibliography -- Index.